2005
DOI: 10.1002/app.22760
|View full text |Cite
|
Sign up to set email alerts
|

pH sensitive interpenetrating network microgels of sodium alginate‐acrylic acid for the controlled release of ibuprofen

Abstract: pH-Sensitive interpenetrating network (IPN) microgels (MGs) of sodium alginate (NaAlg) and acrylic acid have been prepared by using water-in-oil (W/O) emulsion technique. The MGs were characterized by Fourier transform infrared spectroscopy (FTIR), differential scanning calorimetry (DSC), X-ray diffractometer (X-RD). The release of ibuprofen (IB), an anti-inflammatory drug, from these MGs was studied in pH 1.2 and 7.4 media. MG network consists of NaAlg, which disintegrates in the intestinal fluid, while poly(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(28 citation statements)
references
References 20 publications
(12 reference statements)
3
25
0
Order By: Relevance
“…The release rates of NS to an external medium are more difficult compared to the NaAlg microspheres. Similar results can be found from the published reports [16,17]. In the study of Krishna Rao and coworkers, controlled release of cefadroxil from IPN microspheres based on chitosan, acrylamide-graftedpoly(vinyl alcohol) and hydrolyzed acrylamide-graftedpoly(vinyl alcohol) were investigated.…”
Section: In Vitro Release Studysupporting
confidence: 80%
See 1 more Smart Citation
“…The release rates of NS to an external medium are more difficult compared to the NaAlg microspheres. Similar results can be found from the published reports [16,17]. In the study of Krishna Rao and coworkers, controlled release of cefadroxil from IPN microspheres based on chitosan, acrylamide-graftedpoly(vinyl alcohol) and hydrolyzed acrylamide-graftedpoly(vinyl alcohol) were investigated.…”
Section: In Vitro Release Studysupporting
confidence: 80%
“…As the amount of drug increased from 20% to 50%, the % cumulative release rate increased from 26 to 84. This is obvious that as the amount of NaAlg increases in the matrix, diffusion of NS occur faster and higher from the swollen IPN [17]. Ramesh Babu and coworkers prepared IPN microgels of sodium alginate-acrylic acid for the controlled release of ibuprofen.…”
Section: In Vitro Release Studymentioning
confidence: 99%
“…The controlled release of ibuprofen has also been studied through the interpenetrating network of different polymeric microgels of sodium alginate and acrylic acid [19, 20]. For these materials it was reported that a 70% drug release was reached after 6 h and between 85 and 100% after 12.…”
Section: Resultsmentioning
confidence: 99%
“…Functional groups often found in pH sensitive hydrogels are weak acids or bases such as carboxylic acid, phosphoric acid, sulfonic acid and amines [30]. The most frequently studied pH responsive hydrogels are poly(acrylic acid) [70], poly(methacrylic acid) [71], poly(ethylene imine) [72], chitosan [73], poly(L–lysine) [74] and poly(L–histidine) due to the presence of carboxylic or amino groups in these polymers [75]. One of the limitations inherent in synthetic pH-sensitive hydrogels is that they are not biodegradable and therefore must be removed, thereby limiting their in vivo applications [46].…”
Section: Responsive Hydrogelsmentioning
confidence: 99%